Properties of DBD Plasma Jets Using Powered Electrode with and without Contact with the Plasma - Nascimento, Fellype do[UNESP]; Kostov, Konstantin Georgiev [UNESP]; MacHida, Munemasa; Flacker, Alexander (Institute of Electrical and Electronics Engineers (IEEE), 2021)
An experimental investigation comparing the properties of plasma jets in dielectric barrier discharge (DBD) configurations using a powered electrode with and without a dielectric barrier, while keeping a second dielectric barrier over the grounded electrode, is reported in this work. For this purpose, two different power sources were used to produce the plasma jets, with one of them producing a pulsed high-voltage (HV) output and the other one producing a damped sine-wave HV output, which acts as a pulse-like power source. Measurements of plasma parameters were performed for both configurations using argon and helium as working gases. As a result, if the pulsed power source is used, significant differences were found in discharge power ( P-{{mathrm {dis}}} ) and rotational and vibrational temperatures ( T-{r} and T-{v} , respectively) when switching from one configuration to the other. On the other hand, using the pulse-like HV, only the P-{{mathrm {dis}}} parameter presented significant differences when switching the electrode's configuration. For the pulsed source, it has been observed that despite the remarkable increase in P-{{mathrm {dis}}} when changing from the double barrier configuration to the single barrier one, the values obtained for T-{r} and T-{v} also increased, but not in the same proportion as the increase in P-{{mathrm {dis}}} , which suggests a nonlinear dependence between temperatures and discharge power in the plasma jet. As an example for application of plasmas in both configurations, tests in an attempt to remove copper films deposited on alumina substrates were performed and, as a result, there was significant material removal only when the powered electrode was in contact with the plasma. As a general conclusion, if higher power is really required for applications that do not involve in vivo targets, it is better to use this configuration.
Keywords: Atmospheric pressure plasma jets (APPJ); DBD plasma; dielectric barrier discharge (DBD); plasma jets; plasma properties